LIPID PARAMETERS BEFORE AND AFTER IMMUNOBIOLOGICAL THERAPY OF PATIENTS WITH PSORIASIS - Stepanenko, R.L.; Dudchenko, M.O.; Stepanenko, V.I.; Vasylyeva, K.V.; Kameniev, V.I.; Svirid, S.G.; Litinska, T.O. (World of Medicine and Biology, 2022)
Psoriasis is one of the most common dermatoses and occupies one of the leading places among the current problems of modern dermatology. 148 patients were involved in the study. Comparative evaluation of the therapeutic efficacy of monotherapy with the immunobiological drug Adalimumab, as well as its combination with a domestic non-hormonal drug based on natural ingredients (Flaxseed oil, Solidol fatty, D-panthenol, Allantoin, Herd extract, Celandine acid extract, Celandine extract) in the examined patients with psoriasis vulgaris was performed according to the dynamics of regression of cutaneous clinical manifestations of dermatosis: reduction of lesion area, regression of erythema, infiltration, peeling of psoriatic skin rash, changes in PASI, PGA, BSA index. We have proposed a modified treatment regimen for patients with psoriasis vulgaris, which provides a course of systemic immunobiological therapy with adalimumab with concomitant use of domestic non-hormonal drug can increase the effectiveness of treatment and prolong the remission of dermatosis.
Keywords: psoriasis; features of lipid metabolism; immunopathogenesis; immunobiological therapy